Temsil-Taklit İlişkisi Açısından Tasvirin Teorik Zemini_x000D_ -İbnü’l-Arabî’nin Eserleri Esasında- - (:unkn) unknown (My University, 2019)
Tasvir meselesinin kökenindeki sûret ve temsil konusu, başlangıcından günümüzekadar bütün bir felsefe tarihinin de en temel problemidir ve bu yüzden söz konusu tartışmalarda sadece sanata özgü değildir. Tasvirin temsil ve taklit kavramları ile ilişkisi,epistemoloji-ontoloji merkezinde felsefenin, isim-sıfat tartışmaları açısından teolojininve elbette ahlâkın zeminini belirler. Bu makalede tasvir meselesinin felsefe açısındanvarlık ve oluş, teolojik açıdan da yaratma ve kurtuluş kavramlarıyla ilgisi tartışılaraktemsil ve taklidin teorik zemini belirlenmeye çalışılmaktadır. Makale ayrıca meseleninİbnü’l-Arabî metinleriyle nasıl yorumlanabileceğini göstermeyi hedeflemektedir.

The problem of representation and mimesis which is at the roots of the issue of depiction_x000D_ (taswir) is from the beginning until now the most basic problem within the whole_x000D_ body of philosophy and, therefore, arguments in question are not limited to art only. The_x000D_ relation between depiction (taswir) and the concepts of representation and mimesis define_x000D_ the foundations of philosophy in terms of epistemology-ontology, theology with regard_x000D_ to ‘name-designation’ discussions, and, with no doubt, morality. In this article, the connection_x000D_ between the issue of depiction (taswir) and the concepts of “on” and “genesis”_x000D_ is discussed from the point of view of philosophy. In the same time, its connection to the_x000D_ concepts of creation and salvation are examined with regard to theology. Additionally, the_x000D_ author attempts at defining the theoretical foundation of representation and mimesis. Last_x000D_ but not least, the article aims at showing that the issue in question could be interpreted_x000D_ using the books of Ibn al-Arabi.
The Theoretical Foundations of Depiction (Taswir) with Regard to The Relation Between Representation and Mimesis –According to İbn Arabî’s Books-